Cathepsin D: an Mφ‐derived factor mediating increased endothelial cell permeability with implications for alteration of the blood‐retinal barrier in diabetic retinopathy. Issue 4 (30th December 2015) - Monickaraj, Finny; McGuire, Paul G.; Nitta, Carolina Franco; Ghosh, Kaustabh; Das, Arup
Abstract : Inflammation plays an important role in the pathogenesis of diabetic retinopathy (DR). We have previously reported increased monocyte (Mono) trafficking into the retinas of diabetic animals. In this study, we have examined the effect of activated Monos on retinal endothelial cells (ECs). The U937 Mφ‐conditioned medium (CM) significantly decreased the transendothelial resistance of EC monolayers as measured by electric cell‐substrate impedance sensing ( P = 0.007). The CM was fractioned, and the effective fraction (30–100 kDa) was analyzed by liquid chromatography‐mass spectrometry, and cathepsin D (CD) was identified as a major secreted product. Immunoprecipitated CD resulted in decreased resistance in ECs ( P = 0.006). The specificity of CD in mediating alterations of the EC barrier was confirmed using small interfering RNA. The decreased resistance correlated with a significantly increased gap between ECs. CD altered the Ras homolog gene family, member A/Rho‐associated kinase pathway with increased stress actin filament formation in the EC layer. Increased CD levels were found in the retinas of diabetic mice (3‐fold) and serum samples of patients with diabetic macular edema (1.6‐fold) measured by Western blot and ELISA. These findings suggest an important role for Mφ‐derived CD in altering the blood‐retinal barrier and reveal a potential therapeutic target in the treatment of DR.—Monickaraj, F., McGuire, P. G., Nitta, C. F., Ghosh, K., Das, A. Cathepsin D: an Mφ‐derived factor mediating increased endothelial cell permeability with implications for alteration of the blood‐retinal barrier in diabetic retinopathy. FASEB J. 30, 1670–1682 (2016). www.fasebj.org